GAMBARAN PENGETAHUAN AKUPRESUR UNTUK MENINGKATKAN IMUNITAS PADA MAHASISWA DIPLOMA KEPERAWATAN UNIVERSITAS NGUDI WALUYO - Dewi Siyamti; Maksum Maksum (Institut Teknologi Kesehatan Cendekia Utama Kudus, 2022)
Background: Immunity is the ability or endurance of the individuals body responding foreign substances for the body both form inside or outside. Covid-19 is easy to attack on individual who have weak immune system or in vulnerable conditions such as pregnant women, person with comorbid disease, and the elderly. The government continues to strive for handling Covid-19 to cut off the spread and minimize the transmission of the virus, including vaccines and the adaptations of new habit. One of the interventions that can be done independently and can increase the immune is acupressure. Acupressure is useful for relaxation, reducing pain, improving blood circulation, and increase the immunity. With the adoption of new habit adaptations, all activities returned normal including lecturer activity for students. Good immunity is certainly is a must to keep the body healthy. Objective: This research describe the knowledge of acupressure to increase the immunity in Nursing Diploma Students at Ngudi Waluyo University. Method: This research used descriptive quantitative method and uses a total sample of all nursing diploma students. The research was held on March 2022 where students have carried out offline class for laboratory practicum. Result: Based on the analysis of data, it was found that the majority of respondents had less knowledge about acupressure to increase immunity including basic concept, benefits, acupressure points, and how to massage. Conclusion: It can be concluded that the major of respondent have less of knowledge about acupressure for increase the immunity